REPRESENTATION OF HEDONISM IN SOCIAL MEDIA INSTAGRAM - Purnama, Fadhli; Kembara, Getar (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
This research was conducted to determine the representation of hedonism in social media Instagram. Explaining how the representation of hedonism on Awkarin’s Instagram social media is precisely on the Instagram highlights titled Dubai I and Dubai II. The research method used is descriptive qualitative with semiotic analysis based on the theory of Television Codes by John Fiske which is divided into three levels; i.e. Reality level, Representation level, and Ideology level. Using purposive sampling and data collection techniques. At the Reality level, Awkarin’s appearance is considered to show a luxurious life and always having fun. The level of representation there is a message and meaning behind the retrieval techniques and narratives used. At the level of the ideology of extravagance, the pursuit of worldly pleasures, possessing prestigious branded goods, and an instant lifestyle are reflections of hedonistic behavior